SPOTLIGHT on 'Ferrous Pyrometalurgy: A Chalenge for South Africa (The Southern African Institute of Mining and Metallurgy, 1989)
The Technical Programme Committee-Metals Technology of The South African Institute of Mining and Metallurgy, in association with its Vaal Triangle Branch, held a one-day colloquium on 18th April, 1989, the theme being 'Ferous Pyrometalurgy: A Challenge for South Africa'. The venue was the Auditorium 100 at the campus of the Vaal Triangle Technikon in Vanderbijlpark. Project and contract management A Project and Contract Management Conference is to be held on 19th and 20th September, 1989, at the C SIR, Pretoria. Powder metallurgy The PM 90 exhibition is to be held in Wembley, London, from 2nd to 6th July, 1990. The wide range of powders, processing machinery, and powder-metallurgy components at the exhibition will reflect the growth in this highly specialist industry. Castings and forgings Exhibition organizers, FMJ International Publications Ltd, are set to build upon the success of Castings & Forgings '88, which was held as a joint event with Pat- Cast '88. Castings & Forgings '89-with Pat-Cast '89- has already generated a high level of interest, which has been reflected in the demand for stands. Furnaces FURNACES '90, the eighth in this series of exhibitions for the thermal-processing industry, will be held in Solihul, West Midlands, England, on 6th and 7th March, 1990.